Stop Whining! Start Selling!: Profit-Producing Strategies for Explosive Sales Results - Blackman Jeff (Wiley, 2003)
If you want real-world solutions to drive monstrous results, like a 25—50 0ncrease or more in revenue and earnings, Stop Whining! Start Selling! is for you! As a business leader, salesperson, CEO, manager, executive, or entrepreneur, get ready to grow your business, enhance your profits, boost your earnings, and improve your life. Quickly, ethically, and dramatically! This book gives you an almost unfair competitive advantage. It’s loaded with powerful insights and how-to success strategies on: